Analisis Impor Indonesia - Eko Atmadji (Economic Journal of Emerging Markets, 2004)
The analysis of Indonesian foreign trade mainly focused on export analysis. In or¬der to show that import analysis is a crucial need as well, this article analyses Indonesian import applying four analyses instruments which are the degree of import openness, the de¬gree of commodity concentration, the degree of geographical concentration, and autono¬mous and marginal propensity to import analysis. The conclusion is that Indonesian economy is highly import dependence.Keywords:    Import, degree of openness, degree of concentration, Marginal Propensity to Import.